Prevention of Skin Tears in the Dependent Older Person: Contribution of the Humanitude Care Methodology - Melo, Rosa (2018)
Introduction: Aging is characterized by a decline in physical and cognitive functioning, increasing the older person’s vulnerability to dependence. The age factor and the associated physiological skin changes contribute to the occurrence of skin tears. This type of wounds is common in older people and often results from care delivery, hence the importance of caring with Humanitude and avoiding the use of force during interventions. Objectives: This study aims to identify and analyze the current scientific evidence on the contribution of the Humanitude care methodology toward reducing the agitation and preventing skin tears in dependent older people. Methods: Integrative literature review of articles published between 2011 and 2016, available in full text and written in Portuguese and English, in the EBSCOhost and Google Scholar databases. Results: Of a total of 75 articles, five articles were obtained after applying the inclusion and exclusion criteria. Conclusions: The studies showed that the application of the Humanitude care methodology, by using gentle caring techniques, is particularly effective in dependent older people by reducing their pathological agitation behaviors and opposition to treatment/refusal of care and preventing shearing, friction, and bruising.